The Muzara'ah Contract and Its Impact on the Income Stability of Tobacco Farmers: A Study of Justice and Economic Resilience - Muhammmad Ali Fahmi; Riskiyatul Khasanah; Ainul Furqon (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The significance of this study lies in understanding the implementation of the muzara’ah contract in tobacco farming and its impact on farmers’ income stability in terms of fairness and economic resilience. This study employs a descriptive qualitative method using a case study approach. Data were collected through interviews, observations, and documentation from informants selected using snowball sampling, specifically landowners and farmworkers. Data analysis was conducted in three stages: data reduction, data presentation, and data verification. The results indicate that the traditional, oral implementation of the muzara’ah contract based on trust results in a fair 50:50 division of the harvest. This contract enables landless farmers to maintain an income and promotes increased productivity and farmer income. The positive impacts of implementing this contract include improvements in farmers’ income, education, health, and household facilities. Thus, the muzara’ah contract makes a significant contribution to enhancing the well-being and economic resilience of the tobacco-farming community in Jarin Village.